Electrical circuit analogy for analysis and optimization of absorption energy storage systems. (1st June 2016) - Zhao, Tian; Min, Yong; Chen, Qun; Hao, Jun-Hong
Abstract: Due to the rapid development of renewable energy and waste energy recovery, absorption energy storage is an important technology with promising future. However, because most researches focus on working fluid flow rather than energy flow used in electric power systems, it is hard to analyze the entire systems as a whole. This contribution introduces the electrical circuit analogy to analyze absorption energy storage systems from the perspective of energy flow. It turns the energy storage and release processes to their corresponding electrical circuits, which are described by Kirchhoff's laws in circuitous philosophy instead of complex component analysis. On this basis, optimization of an absorption energy storage system is converted to a conditional extremum problem, and applying the Lagrange multiplier method offers the optimization equations to directly obtain the optimal structural and operating parameters with the best performance. In this contribution, the optimized results offer 13% and 25% higher power in the storage and release cases, respectively, compared to existing experimental results. Besides, inspired from the batteries connected in parallel and series, the design of a multi-stage absorption energy storage system could store low-grade heat but provide high-grade heat, which further reveals the superior of the newly proposed approach. Graphical abstract: Instead of the perspective of fluid flow, this paper introduce the electrical circuit analogy of absorption energy storage systems from the perspective of energy flow. Utilization of circuitous philosophy gives a new way to analyze absorption energy storage systems, which has great potential in optimization of the entire thermal and electric energy utilization systems for further energy conservation. Highlights: Analyze absorption energy storage systems inspired from circuitous philosophy. Introduce electrical circuit analogy for absorption energy storage systems. Obtain the inherent relation of each parameter by circuitous philosophy. Derive the optimization equations by the conditional extremum method. Over 13% performance improvement is obtained by the optimization method.